2014
DOI: 10.18488/journal.29/2014.1.4/29.4.30.38
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Human Capital on Economic Growth: Evidence from Tunisia Using Star and Stecm Models

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Constant relationship among productivity, human capital, and interior innovation capabilities indicated the importance of human capital for Portugal's economy. Mgadmi and Rachdi (2014) conducted an empirical finding in Tunisia from 1974 to 2012. They concluded that the non-linear relationship between human capital (HC) and growth and HC significantly influenced economic growth.…”
Section: Economic Growth and Human Capitalmentioning
confidence: 99%
“…Constant relationship among productivity, human capital, and interior innovation capabilities indicated the importance of human capital for Portugal's economy. Mgadmi and Rachdi (2014) conducted an empirical finding in Tunisia from 1974 to 2012. They concluded that the non-linear relationship between human capital (HC) and growth and HC significantly influenced economic growth.…”
Section: Economic Growth and Human Capitalmentioning
confidence: 99%